Remaining Service Life Discharge Conveyor E pada Tambang Batubara PT XYZ di Kabupaten Tebo, Provinsi Jambi - Jossie Indra Saputra; Elfida Moralista; Iswandaru (Bandung Conference Series: Mining Engineering, 2023)
Abstract. Carbon steel is the widely used steel as a material for conveyor structures. conveyor structure interacts with the environment can cause corrosion Therefore, monitoring is needed, one of which is by conducting a study on corrosion on the conveyor structure so that the remaining service life of the structure can reach its design life. This study aims to determine the type of corrosion, the applied corrosion control method, the corrosion rate, and the remaining service life of the conveyor structure. The methodology in this research is the method of measuring the thickness reduction of the conveyor structure at 32 observation points along 142 meters above the ground. In this study, observations of environmental conditions included air temperatures ranging from 25.8oC – 26.64oC with an average humidity of 88.5% and rainfall ranging from 42.19 – 437.7 mm.The type of corrosion that occurs in the conveyor structure is uniform corrosion. The corrosion control method applied is the coating method with using Seaguard 5000 for primary coating, Sherglass FF for intermediate coating, Aliphatic acrylic modified polyurethane for top coating. Abstrak. Baja karbon merupakan baja yang banyak digunakan sebagai bahan pembuatan struktur conveyor. struktur conveyor yang berinteraksi dengan lingkungan dapat mengakibatkan terjadinya korosi Oleh karenanya, diperlukan monitoring salah satunya dengan melakukan kajian mengenai korosi pada stuktur conveyor agar sisa umur pakai struktur dapat mencapai umur desainnya. Penelitian ini bertujuan untuk mengetahui jenis korosi, metode pengendalian korosi yang diaplikasikan, laju korosi, dan sisa umur pakai struktur conveyor. Metodologi dalam penelitian ini yaitu metode pengukuran pengurangan ketebalan struktur conveyor pada 32 titik pengamatan sepanjang 142. Pada penelitian ini, pengamatan kondisi lingkungan meliputi temperatur udara berkisar 25.8oC – 26.64 oC dengan kelembaban rata-rata 88,5% dan curah hujan berkisar 42.19 – 437.7 mm. Jenis korosi yang terjadi pada struktur conveyor adalah korosi merata. Metode pengendalian korosi yang diaplikasikan adalah metode coating dengan menggunakan Seaguard 5000 untuk primer coating, Sherglass FF untuk intermediate coating, Aliphatic acrylic modified polyurethane untuk top coating.